О выборе инвариантов тензора напряжений при уточнении определяющих уравнений механики деформируемого твердого тела для изотропных материалов - Золочевский, Александр Алексеевич (НТУ "ХПИ", 2007)
Розглянута роль інваріантів тензору напружень в узагальнених визначальних співвідношеннях для нелінійного деформування ізотропних материалів. Проаналізовані експериментальні дані для складного напруженого стану. Розглянуті закономірності пошкоджуваності ізотропних материалів. Сформульовані практичні рекомендації.

A role of the invariants of the stress tensor in the generalized constitutive equations of the nonlinear deformation for the isotropic materials has been considered. The experimental data at the complex stress state conditions have been analyzed. Principal features of the damage for the isotropic materials have been given. Practical recommendations have been formulated.
Keywords: нагружение; закон деформирования; легкие сплавы; порошковые материалы; напряженное состояние